Modulation of Erythrocyte Plasma Membrane Redox System Activity by Curcumin - Prabhakar Singh; Rajesh Kumar Kesharwani; Krishna Misra; Syed Ibrahim Rizvi (Biochemistry Research International)
Plasma membrane redox system (PMRS) is an electron transport chain system ubiquitously present throughout all cell types. It transfers electron from intracellular substrates to extracellular acceptors for regulation of redox status. Curcumin, isolated from Curcuma longa, has modulatory effects on cellular physiology due to its membrane interaction ability and antioxidant potential. The present study investigates the effect of curcumin on PMRS activity of erythrocytes isolated from Wistar rats in vitro and in vivo and validated through an in silico docking simulation study using Molegro Virtual Docker (MVD). Effects of curcumin were also evaluated on level of glutathione (GSH) and the oxidant potential of plasma measured in terms of plasma ferric equivalent oxidative potentials (PFEOP). Results show that curcumin significantly (p<0.01) downregulated the PMRS activity in a dose-dependent manner. Molecular docking results suggest that curcumin interacts with amino acids at the active site cavity of cytochrome b5 reductase, a key constituent of PMRS. Curcumin also increased the GSH level in erythrocytes and plasma while simultaneously decreasing the oxidant potential (PFEOP) of plasma. Altered PMRS activity and redox status are associated with the pathophysiology of several health complications including aging and diabetes; hence, the above finding may explain part of the role of curcumin in health beneficial effects.